Kontribusi Pengetahuan Kalimat Efektif terhadap Kemampuan Menulis Surat Resmi Siswa Kelas VIII SMPN 1 Pariangan - Angraeni, Sesti Dwi; Ratna, Ellya; Afnita, Afnita (Universitas Negeri Padang, 2013)
This study aims to determine the contribution of knowledge to the ability to write effective sentences formal letter eighth grade students of SMP N 1 Pariangan. This research is quantitatively using correlation. The population was eighth grade students of SMP Negeri 1 registered Pariangan school year 2012/2013 with a number of 108 people scattered in five classes. The research sample amounted to 25 people who were taken from 25% of the population. Because the subject of research of more than 100 students, appropriate sampling technique that is proportional random sampling technique. Proportional random sampling sampling in proportion to the number of students per class. . The results showed that there was an effective contribution to the knowledge of the sentence formal letter writing skills by 6.7%, while the rest is influenced by other factors not examined in this study.